Depleted Leukocyte Mitochondrial DNA Copy Number in Metabolic Syndrome - Ching-Hui Huang; Shih‐Li Su; Ming‐Chia Hsieh; Wen‐Ling Cheng; Chia‐Chu Chang; Hsi-Lin Wu; Chen‐Ling Kuo; Ta‐Tsung Lin; Chin‐San Liu (2011)
Aims: Metabolic syndrome (MetS) is characterized by a group of defects of metabolic origin which are possibly involved in mitochondrial DNA (mtDNA) alteration of mtDNA content [Lee et al. Exp Biol Med, 2007; 232(5):592-606]. The present study was undertaken to ascertain whether alteration of leukocyte mtDNA copy number is related to MetS.Methods: Eighty non-MetS subjects and 50 subjects with MetS were recruited. The mtDNA copy number of leukocytes from each group of subjects was measured using quantitative polymerase chain reaction.Results: The mtDNA copy number of leukocytes in subjects with MetS was significantly lower than that of non-MetS subjects. Depleted mtDNA copy number is correlated with lower plasma HDL, higher triglyceride, higher HOMA-IR and hypertension, and is even more sensitive to MetS criteria.Conclusions: Depleted leukocyte mtDNA copy number is related to the severity of MetS. Alteration of mtDNA copy number in leukocytes is proposed as a MetS biomarker involved in the bioenergetic change of mitochondria.